Analisis dan Perancangan Sistem Informasi Manajemen Penilaian P5 Pada SMK Permata Harapan - Miftahul Ilmi; Robert Situmorang; Doni Syofiawan (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2025)
The Merdeka Curriculum implemented in Indonesia aims to strengthen the formation of the Pancasila student profile through the P5 Program. This program prioritizes project-based learning across disciplines to develop students' character. This research aims to develop a management information system for P5 at SMK Permata Harapan, which will support the learning and assessment processes in the implementation of the Merdeka Curriculum. The research method used is Research and Development (R&D) with a waterfall development model, which consists of the stages of requirement gathering, design, coding, testing, and maintenance. The proposed system involves users with different roles, including students, teachers, principals, and admins. The results of the alpha test showed that all features of the P5 management information system functioned well, while the beta test through a questionnaire on 30 teachers received a positive assessment with an average score of 4.6, indicating that the P5 management information system is very feasible to implement. This study concludes that the P5 management information system can support the implementation of the Merdeka curriculum and help teacher performance in managing learning and assessment.